Does relatedness drive the diversification of countries` success in sports? - Knuepling, L.; Broekel, T. (European Sport Management Quarterly, 2020)
Research Question: The sources of countries` success in sporting events have been investigated for a long time. In addition to socioeconomic factors, sport specialization and competitive balance have been identified as impacting medal yields. Nevertheless, there remains little understanding of how countries become successful in sports they did not succeed in before.